The effect of 25% Mauli banana stem extract gel to increase the epithel thickness of wound healing process in oral mucosa - Maharani Laillyza Apriasari; Ariska Endariantari; Ika Kustiyah Oktaviyanti (Dental Journal (Majalah Kedokteran Gigi), 2015)
Background: Mauli banana is a special plant of South Borneo that can be used as alternatif medicine for wound healing wound healing. Recent studies showed that Mauli banana stem contained some compound such as flavonoid, saponin, and tannin that had antibacterial and antiinflamation effect, and can accelerate the wound healing. Purpose: This study was aimed to know the effect of 25% Mauli banana extract gel to the epithel thickness of wound healing process in oral mucosa. Method: It was the real experimental with post test only control group design. It used 36 Sprague dawley rats that divided into 3 groups: the negative control group by giving aquadest, the positive control group by giving drug contain Aloe vera, and the treatment group by giving 25% ethanol extract of Mauli banana stem. Biopsy was done on day 3, 5, 7 and the preparat was made to measure the thickness of oral mucosa epithel by Image J software. Result: The result showed that 25% ethanol extract of Mauli banana stem can increased the thickness of oral mucosa epithel on third day (51.26 µm), fifth days (108.49 µm), and seventh day (170.66 µm). The top thickness of mucosa epithel was on the seventh day. Two-ways Anova and Post Hoc LSD (p<0.05) showed the significant different between aquadest and 25% ethanol extract of Mauli banana stem. 25% ethanol extract of Mauli banana stem and drug contains Aloe vera are the aqual of meaningfull. Conclusion: 25%ethanol extract of Mauli banana can increase the epithelial thickness of wound healing procces in oral mucosa.